2021
DOI: 10.20945/2359-3997000000372
|View full text |Cite
|
Sign up to set email alerts
|

Performance of adiposity indicators in predicting metabolic syndrome in older adults

Abstract: Objective: To evaluate the association between some indicators of adiposity and markers of metabolic disorder, evaluate their performance in predicting metabolic syndrome (MetS), and identify their cutoff values among older adults, both in the overall sample and according to sex. Subjects and methods: Cross-sectional study in 159 older men and women. MetS was defined according to the harmonized criteria. The assessments included waist circumference (WC), waist-to-height ratio (WHtR), conicity index (C index), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Similarly, in a systematic literature review in 2016, Corrêa et al ( 61 ) also shows that WHtR has better performance than WC and BMI in evaluating MetS. Alves et al's ( 62 ) study shows that LAP, WC, and WHtR indicators identify MetS in older women and can be used to assess and monitor MetS individually or collectively.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, in a systematic literature review in 2016, Corrêa et al ( 61 ) also shows that WHtR has better performance than WC and BMI in evaluating MetS. Alves et al's ( 62 ) study shows that LAP, WC, and WHtR indicators identify MetS in older women and can be used to assess and monitor MetS individually or collectively.…”
Section: Discussionmentioning
confidence: 97%
“…The study characteristics and outcome definitions of 17 included studies with a total of 74,520 participants are shown in Table 1 [ [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ]. All studies were published from 2014 to 2021.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published from 2014 to 2021. Four studies were conducted in Brazil [ 26 , 35 , 37 , 39 ], 5 in China [ 28 , 30 , 33 , 34 , 42 ], 1 in Colombia [ 40 ], 2 in Iran [ 27 , 36 ], 2 in Japan [ 31 , 32 ], 1 in Singapore [ 41 ], 1 in Spain [ 29 ], and 1 in Thailand [ 38 ]. Sample sizes ranged from 159 to 24,215 participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations